The inhibition of restriction endonuclease PvuII cleavage activity by methylation outside its recognition sequence. - Chen, D F (1991)
The recombinant plasmid pGEM4Z-ras DNA which was methylated on dam and dcm sites outside the PvuII recognition sequence was digested with restriction endonuclease PvuII, and one of the three PvuII sites was about 16-fold less efficient to cleave than either of the other two. On the contrary, the three PvuII sites were cleaved at about the same rate on the unmethylated DNA molecule. The results show that the cleavage inhibition of the methylated DNA on the certain PvuII site was caused by methylation outside the PvuII recognition sequence. Maybe a adjacent methylated dam site *A was responsible for the less efficient cleavage. This observation suggests that methylation outside the recognition sequence may be considered a new factor in the kinetic experiment of restriction endonuclease.